AWARENESS OF MEDICAL SPECIALISTS AND PATIENTS IN BULGARIA OF ETHICS COMMITTEES AND THE BENEFITS OF THEIR WORK - Neli Gradinarova; Tihomira Zlatanova (Peytchinski Publishing, 2018)
In today's healthcare, the role of morality emerges to the forefront as a result of the high degree of uncertainty in our modern environment. Ethically responsible behaviour is therefore perceived as a prerequisite for preventing and counteracting a number of moral risks in society. With regard to moral hazard and responsibility, ethical codes represent a rational control mechanism, lowering the extent of the probability of moral peril. Ethics committees are also founded based on such ethical codes, the purpose of such committees being the proclamation and observation of the principles and norms set forth. At the healthcare institutions of the Republic of Bulgaria, ethics committees are established that are based on the principles of medical ethics and medical law. The significance with which ethics committees are charged regarding the sustainable development of the healthcare system consists of protecting the patients, the medical professionals and the institution itself. Awareness of the significance, functions and benefits of ethics committees and their impact on the medical practice and patients in Bulgaria is, however, insufficiently low. In a questionnaire survey conducted among 149 medical specialists employed at three medical establishments for hospital care in the country, and 269 patients under treatment at them, at being asked "Do you think that ethics committees contribute to protecting and respecting patients' rights?", 26.2% of the respondents among the medical professionals replied that they are not sure, while 25.7% of did not provide an answer to the question thus asked due to being unfamiliar with ethics committees as an institutionalized body and their functions. The analysis of the results of the abovementioned survey among medical professionals and patients evidences a low level of awareness of the ethics committees and their work on the territory of the Republic of Bulgaria. It is essential for healthcare establishments to enhance their education and information channels with regard to the existence of ethics committees and the benefits of their work. Such a change would lead to improving the quality of healthcare services provided and the overall health of the nation.